Keanekaragaman laba-laba pada perkebunan kelapa sawit yang berbatasan dengan hutan - Ulka Sri Asih; Yaherwandi Yaherwandi; Siska Efendi (Perhimpunan Entomologi Indonesia, 2021)
Oil palm plantations bordering forests were thought to affect the biotic components that make up the diversity of ecosystems, especially species with high mobilization and adaptability, such as spiders. This study aims to identify spiders found in oil palm plantations and analyzing diversity and evenness at various distances of oil palm plantations from the forest. Observations of spiders were carried out on oil palm plantations bordered by forests in Nagari Gunung Selasih and Sungai Kambut, Pulau Punjung District, Dharmasraya Regency, West Sumatra Province. In oil palm plantations, a one km long transect line was made from the forest edge. In the sample plots, spiders were observed using a pitfall trap, knockdown, and hand collecting. Data were analyzed using the Shannon-Wiener diversity and evenness index. The highest spider species diversity index was found at a distance of 100–300 m from the forest, respectively 3.06, 3.05, and 3.11. The same is true for the highest evenness index at a distance of 100–300 m from the forest, respectively, namely 0.94, 0.94, and 0.95. In general, the results of this study indicate that the presence of forest bordering the forest is thought to affect spiders in oil palm plantations.